2015
DOI: 10.4314/jfas.v7i3.10
|View full text |Cite
|
Sign up to set email alerts
|

Unconstrained melting and solidification inside rectangular enclosure

Abstract: The present study concerns with the numerical study of unconstrained solidification and melting of phase change material (PCM) inside a two dimensional open rectangular cavity.The Cavity is filled by RT-27 as phase change material and air. Numerical study is carried out for different cavity aspect ratios. Result indicates that the conduction heat transfer is dominant at initial time of melting process where the layer of liquid PCM near hot surface is so thin.Solid PCM sinks to bottom of cavity due to higher de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Thus, heat conduction decreases by increasing the thickness of the solid layer. The solidification rate reduces gradually during the process, especially near the end of process where the solid layer covers the whole of the capsule except a small region [33]. In both the freezing and melting experimentations, it was observed that the addition of nanoparticles enhanced the freezing and melting rates, and the maximum enhancement was observed with the 0.5% volume percentage of GnP.…”
Section: Melting Processmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus, heat conduction decreases by increasing the thickness of the solid layer. The solidification rate reduces gradually during the process, especially near the end of process where the solid layer covers the whole of the capsule except a small region [33]. In both the freezing and melting experimentations, it was observed that the addition of nanoparticles enhanced the freezing and melting rates, and the maximum enhancement was observed with the 0.5% volume percentage of GnP.…”
Section: Melting Processmentioning
confidence: 92%
“…Thus, as the thickness of the liquid layer increases, the heat transfer conduction is reduced, and conversely the natural convection is enhanced. Therefore, melting is accelerated because of this natural convection in the liquid [33].…”
Section: Melting Processmentioning
confidence: 99%